Temporal and Diel Variability of Mesozooplankton Abundance in the Central Red Sea with Emphasis on the Calanoid Copepod Centropages spp. - S. Al-Harbi, Hanan (Journal of King Abdulaziz University: Marine Sciences, 2022)
The temporal and diel variability in mesozooplankton abundance were studied between January and December 2018 at a station in front of Obhur Creek, central Red Sea. Temperature and salinity reflected the hot and saline conditions of the Red Sea. Inorganic nutrients and phytoplankton biomass (chlorophyll a) depicted the oligotrophic characteristics of the region with occasional increase. Phytoplankton displayed low numerical densities (average 246.80±306.98×103 cells m-3) except for the high value in May (1082.34×103 cells m-3). Diatoms dominated the total phytoplankton (70.6%) most of the year, while dinoflagellates during summer. The mesozooplankton average abundance varied temporally between 1523±1377 in February and 23171±9704 individuals m-3 in December, while diel values fluctuated between 2694±3482 and 9009±6851 individuals m-3. The seasonal abundance was the higher in cold period; while the high diel abundance appeared mainly from the evening and midnight collections. Copepods were the dominant group, contributing 79.5 % to total zooplankton. Cladocerans, chaetognaths, appendicularians and crab larvae were represented considerable percentages of total zooplankton (4.8, 1.7, 1.5 and 2.8%, respectively). All of these groups exhibited clear seasonal and diel variations. The dominant calanoid copepod Centropages spp. attained its high abundance during the spring and autumn, but it recorded the highest diel from the evening and midnight. It is evident from this study that the distribution of zooplankton in the central Red sea is mainly dependent on the cumulative effect of both temperature and solar radiation, while the Centropages spp. have a particular affinity towards the moderate temperature indicating its native behavior.